Beban kerja dan kinerja karyawan: studi pada divisi sumber daya manusia PT Kereta Api Indonesia (persero) - Anggraeni, Dewi; Gaffar, Mohammad Rizal (Journal of Management and Digital Business, 2025)
This study aims to assess the workload experienced by employees in the Human Resources Division at PT Kereta Api Indonesia (Persero) headquarters and to analyze how workload affects employee performance. Workload is an important factor influencing performance because excessively high workloads can negatively affect productivity, effectiveness, and employees' physical and mental health. The study uses a quantitative approach with total sampling, involving the entire population of 107 employees as respondents through a questionnaire survey. The questionnaire was developed using a Likert scale to measure respondents' perceptions. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that employees' workload is relatively high, which may contribute to declines in both productivity and work quality. In addition, the analysis shows a positive, statistically significant relationship between workload and employee performance: increases in workload are associated with higher perceived pressure, leading to suboptimal work outcomes.